Réponses

  • Utilisateur Brainly
2014-06-17T18:02:00+02:00
(-3)-5-(2+7)+(-3) =
-3-5-(9)-3 =
-3-5-9-3 = -20

(-7)-(7-(-4))+(-5)-8 =
-7-(7+4)-5-8 =
-7-11-5-8 = -31

-6+9-4 =
-10+9 = -1

6-9-4 =
6-13 = -7

(-6)-9-4 =
-6-9-4 = -19

(-4)-8+12 =
-4-8+12 =
-12+12 = 0


2014-06-17T18:03:48+02:00
(-3)-5-(2+7)+(-3)
= - 3 - 5 - 2 - 7 - 3
= - 20

(-7)-(7-(-4))+(-5)-8
= - 7 - 7 + 4 - 5 - 8
= - 7 - 7 - 5 - 8 + 4
= - 27 + 4
= - 23

6-9+4
= 6 - 9 + 4
= 6 + 4 - 9
= 10 - 9
= 1

(-6)+9-4
= - 6 + 9 - 4
= - 6 - 4 + 9
= - 10 + 9
= - 1

6-9-4
= 6 - 9 - 4
= 6 - 13
= - 7

(-6)-9-4
= - 6 - 9 - 4
= - 19

(-4)-8+12

= - 4 - 8 + 12
= - 12 + 12
= 0